Problems and prospects of Kazakhstan processing industry. (Journal of Economic Research & Business Administration, 2015)
Currently, Kazakhstan is a topical issue on the development and support of manufacturing enterprises. Problems processing industry - a factor that depends on the internal market potential, the degree of access to the markets of neighboring countries on the investment attractiveness of the non-oil sector as compared to the oil and gas and metallurgical industry. During the last period in the country there is a positive dynamics in the development of the industry. In the structure of manufacturing the highest production figures account for metallurgy, chemical industry and mechanical engineering.
Keywords: Problems and prospects; manufacturing